ANALISIS KINERJA ORGANISASI DINAS KEBAKARAN KOTA SEMARANG - Parameswari, Palupi; Nurcahyanto, Herbasuki; Rihandoyo, Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The increase in population has always been follow by the rapid construction of buildings and settlements. With the increasing density of settlements and bulidings, fire risk become higher. Competent authorities to prevent and deal with disaster fire firefighter is an institution. In Semarang competent institution os Fire Department of Semarang. This study was carried out based on the problems that occur in the implementation of programs and activities of the Fire Department of Semarang. the purpose of this study was to analyze the performance of Semarang Fire Department and identify factors supporting and inhibting performance Semarang Fire Department as a firefighter institution. Performance assessment Semarang Fire Department visits of inputs, service quality, efectiveness, and responsiveness. While the factors that affect the performance seen from the structure of the organization, cooperation, and infrastructure. This study used a qualitative descriptive informant derived from Semarang Fire Department employees and from people lived in Semarang. Based on research, the performance of Semarang Fire Department has not been optimal. Therfore, some recommendations can be given to optimizing the use of energy performance such as outsourching and additonal training and education to employees. Immediately prepare Standard Operating Procedure (SOP) to minimize errors. Improved employee competence and completeness of infrastrucuture. Provides the means to be able to accomodate the aspirations of the people.